MEMOIRS BOOK: III INTERNATIONAL COLLOQUIUM ON AGROECOLOGY, Driving Sustainable Agrarian Transformation for World Environment Day (2025)
The Third International Agroecology Colloquium at the University of Pamplona stands as a collective effort to strengthen the exchange of knowledge and experiences among researchers, teachers, students, and producers focused on more resilient and sustainable agricultural models. This event, which included keynote lectures and presentations, consolidated a valuable collection of reflections on agroecology as a science, movement, and practice for the sustainable development of global food systems. The University of Pamplona, as a leader in Colombia in promoting agroecology, reaffirmed its commitment to sustainability and agroecological innovation, training professionals dedicated to the social and economic transformation of the country. During the event, fundamental topics such as agroforestry systems, the importance of arbuscular mycorrhizae, and agroecological soil management were discussed. Additionally, research on crop nutrition, soil biodiversity, and the use of information technologies in agricultural extension was addressed. The presentations highlighted advancements in the use of bioinputs, biological pest control, and fertilization optimization. There was a growing interest in sustainability, reducing the use of agrochemicals, and improving resilience to environmental challenges. This Memoirs book not only documents these contributions but will also serve as a key resource for future research, teaching, and agroecological extension strategies.
Keywords: Agroecology; Sustainability; Soil management; Bioinput